Music as a Mnemonic to Learn Gesture Sequences in Normal Aging and Alzheimer’s Disease - Moussard, Aline; Bigand, Emmanuel; Belleville, Sylvie; Peretz, Isabelle (Frontiers in Human Neuroscience, 2014)
Strong links between music and motor functions suggest that music could represent an interesting aid for motor learning. The present study aims for the first time to test the potential of music to assist in the learning of sequences of gestures in normal and pathological aging. Participants with mild Alzheimer's disease (AD) and healthy older adults (Controls) learned sequences of meaningless gestures that were either accompanied by music or a metronome. We also manipulated the learning procedure such that participants had to imitate the gestures to-be-memorized in synchrony with the experimenter or after the experimenter during encoding. Results show different patterns of performance for the two groups. Overall, musical accompaniment had no impact on the Controls' performance, but improved those of AD participants. Conversely, synchronization of gestures during learning helped Controls but seemed to interfere with retention in AD. We discuss these findings regarding their relevance for a better understanding of auditory-motor memory, and we propose recommendations to maximize the mnemonic effect of music for motor sequence learning for dementia care.